Sistemski pristop k obvladovanju raznolikosti zaposlenih v globalnem okolju - Treven, Sonja (Organizacija (Kranj), 2005)
In the paper the authors first define the term diversity of employees. They then turn their attention to its elements, like various types of personality, values and attitudes of employees, the family question, and demografic trends that managers should know in order to manage the diversity of the employees in their organization successfully. They also brief different manners and methods of management diversity. Authors find that successful management of diversity depends on holism, which in turn depends on systems thinking, although different versions of it support holism differently. The dialectical system approach is what authors find most suitable among various approaches, because it supports interdisciplinarity of work best of all, including work and co-operation of diverse ones.
Keywords: corporation; podjetje; kadri; zaposleni; človeški viri; vrednote; kadrovski management; teorija sistemov